Conductive hydrogel adhesive with temperature phase change characteristic for fixing skin electrode

By optimizing the structural composition of the conductive hydrogel adhesive, the problems of insufficient conductivity and mechanical properties in the existing technology have been solved, achieving firm adhesion and reversible phase transition of the electrode, improving the stability and conductivity of the electrode, and making it suitable for various electrode types.

CN120944479AActive Publication Date: 2025-11-14WENZHOU INST UNIV OF CHINESE ACAD OF SCI

Patent Information

Application Number
CN202511476448.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-16
Publication Date
2025-11-14
Estimated Expiration
2045-10-16

AI Technical Summary

Technical Problem

Existing conductive hydrogel adhesives cannot simultaneously satisfy good mechanical strength, adhesion, conductivity and temperature phase change capability when fixing epidermal electrodes, and they also have problems with toxicity and lack of temperature phase change.

Method used

By introducing a variety of structural components with phase change properties, the conductive hydrogel adhesive is optimized and compounded, including natural polymers such as gelatin, collagen, and agar, and conductive substances such as sodium chloride and silver nanoparticles, to form an adhesive with reversible phase change function, ensuring that it can be applied to the skin in liquid form at 50 degrees and cured at body temperature.

Benefits of technology

It achieves strong electrode adhesion, excellent conductivity and reversible phase transition, improves electrode stability, has low material cost, is environmentally friendly, easy to use, and is suitable for various electrode types.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944479A_ABST
    Figure CN120944479A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive adhesives, in particular to a conductive hydrogel adhesive with a temperature phase change characteristic for fixing a skin electrode, and the conductive hydrogel adhesive comprises the following components in parts by weight: 5-20 parts of a structural component; the gel is selected from at least one of gelatin, collagen, agar, chitosan, sodium alginate, gellan gum, methyl cellulose and xanthan gum; 1-5 parts of a conductive substance; 5-10 parts of a water retention component; and 50-70 parts of water. The prepared adhesive has excellent adhesive performance and conductivity, the material cost is low, the adhesive is green and environmentally friendly, the use method is simple and convenient, and optimal use of most electrodes in the market can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive hydrogel adhesives, and more specifically to a conductive hydrogel adhesive with temperature phase change characteristics for fixing epidermal electrodes. Background Technology

[0002] Adhesives are used at the interface of two substances to bond them together. Bonding conductive materials, in particular, requires the adhesive to possess adhesive properties, conductivity, and a certain degree of mechanical strength. Existing adhesives bond two materials together through interfacial adhesion and cohesion, and mainly include epoxy resins, polyacrylic acids, and polyurethanes. Their application process primarily relies on coating with polymer monomers or oligomers, followed by waiting for the materials to polymerize or dry before bonding.

[0003] CN119242253A discloses a hydrogel adhesive for battery negative electrodes. This invention features a chain-entangled foam structure, which effectively solves the expansion problem of Si-based negative electrodes and improves battery cycle life and cycle stability. However, this hydrogel adhesive lacks the ability to undergo a temperature phase change and cannot be used for bonding and peeling skin electrodes.

[0004] CN114149753A describes a hydrogel adhesive suitable for underwater use. Before curing, this hydrogel adhesive comprises liquid A and liquid B. An initiator in liquid A forms a redox initiation system with a reducing agent in liquid B, initiating in-situ polymerization and crosslinking of water-soluble monomers. This forms an interpenetrating network structure with the water-soluble polymer chains, achieving rapid and strong adhesion. However, this adhesive lacks temperature-dependent phase transition capability and electrical conductivity; bonding electrodes with it can cause the electrodes to malfunction.

[0005] Conductive hydrogel adhesives require good mechanical strength, excellent adhesion, suitable operating temperature, and appropriate conductivity. Current technologies primarily rely on polymer polymerization or in-situ curing of hydrogels for electrode bonding, which generally suffers from the problem that conductivity and mechanical properties cannot simultaneously meet the requirements of electrode bonding. Furthermore, current adhesives often exhibit issues such as toxicity and lack of temperature-dependent phase transitions. Summary of the Invention

[0006] Therefore, the purpose of this invention is to provide a conductive hydrogel adhesive with temperature phase change characteristics for fixing epidermal electrodes. Through optimized compounding of structural components, a synergistic effect of strong adhesion, excellent conductivity, and reversible phase change is achieved, thereby improving the stability of the electrode in use.

[0007] This invention constructs a hydrogel adhesive by introducing multiple structural components with phase change properties. Through optimized compounding of these components, the adhesive exhibits high mechanical strength and good adhesion, enabling it to firmly bond to the electrodes. Simultaneously, the introduced conductive components possess excellent conductivity, ensuring the proper functioning of the electrodes.

[0008] Unlike conventional adhesives, the adhesive provided by this invention possesses temperature phase change properties, adhesion, and conductivity simultaneously. The adhesive is solid under normal conditions but melts into a liquid state when heated to 50 degrees Celsius. The liquid adhesive is applied to the interface of a conventional electrode on the skin, and upon cooling to body temperature, it reverts to a solid state, adhering the electrode to the skin. Because the adhesive itself has excellent conductivity, it does not interfere with the detection of various signals from the skin by the conventional electrode.

[0009] The adhesive provided by this invention comprises a structural component, a conductive substance, water, and a water-retaining component. The structural component consists of natural polymers (such as proteins and polysaccharides) with reversible phase transition properties, enabling the adhesive to possess reversible temperature phase transition capabilities. It uses natural polymers (proteins / polysaccharides) with reversible phase transition properties, such as gelatin, collagen, and agar, as its core, and regulates the phase transition temperature and adhesion performance through compounding. The conductive substance and components are rationally combined and proportioned to achieve optimized water retention and conductivity. The prepared adhesive exhibits excellent adhesion and conductivity, is low-cost, environmentally friendly, and easy to use, promoting the optimized application of most electrodes on the market.

[0010] The technical solution of the present invention is as follows: <First Aspect> A conductive hydrogel adhesive with temperature phase change properties for fixing epidermal electrodes comprises the following components in parts by weight: Structural components, 5-20 parts; selected from at least one of gelatin, collagen, agar, chitosan, sodium alginate, gellan gum, methylcellulose, and xanthan gum; 1-5 parts of conductive material; 5-10 parts of water-retaining component; 50-70 parts water.

[0011] The water-retaining component is selected from at least one of betaine, sodium citrate, glycerin, ethylene glycol, propylene glycol, sodium tripolyphosphate, ectoine, sodium pyrrolidone carboxylate, trehalose, and nicotinamide.

[0012] The conductive material is selected from at least one of sodium chloride, lithium chloride, potassium nitrate, and silver nanoparticles.

[0013] Preferably, the conductive material and the water-retaining component satisfy one of the following combinations: (A) A combination of betaine and sodium chloride; (B) Combination of sodium citrate and potassium nitrate; (C) Combination of betaine and silver nanoparticles.

[0014] The combination of betaine and sodium chloride can improve the mobility of free ions; the combination of sodium citrate and potassium nitrate can improve the concentration of free ions; and the combination of betaine and silver nanoparticles can construct an interconnected three-dimensional conductive network and form a synergistic conductive pathway. All of these preferred combinations can improve the conductivity of the adhesive and reduce the tightness during gel application.

[0015] Preferably, the structural components are one of the following combinations: (a) Gelatin and agar, in a weight ratio of (1-5):1; (b) Gelatin and gelatin, compounded in a weight ratio of (2-8):1; (c) Collagen and xanthan gum, compounded in a weight ratio of (2-4):1; (d) Gelatin and sodium alginate, compounded in a weight ratio of (1-3):1.

[0016] <Second aspect> A method for preparing the conductive hydrogel adhesive as described above includes the following steps: (1) Add the water-retaining component and the conductive substance to water and stir physically until completely dissolved to obtain a premixed solution; (2) Add the structural component to the premixed solution and stir to form a uniform dispersion; (3) Heat the dispersion to a certain temperature and stir at that temperature for 30-60 minutes; (4) Cool to room temperature to form a gel.

[0017] In step (3), the specific heating conditions are as follows: When the structural component is gelatin, heat to 60-70 degrees Celsius. When the structural component is collagen, heat to 40-60 degrees Celsius. When the structural component is agar, heat to 90-100 degrees Celsius. When the structural component is sodium alginate, heat to 60-80 degrees Celsius. When the structural component is gellan gum, heat to 80-100 degrees Celsius. When the structural component is xanthan gum, heat to 80-90 degrees Celsius.

[0018] When the structural components are a mixture of gelatin and agar, they are dissolved at 90 degrees Celsius; a mixture of gelatin and gellan gum is dissolved at 80 degrees Celsius; a mixture of collagen and xanthan gum is dissolved at 80 degrees Celsius; and a mixture of gelatin and sodium alginate is dissolved at 70 degrees Celsius. These compounding schemes can enhance the adhesion and mechanical strength of the adhesive and improve wearing comfort by adjusting the hydrophilic-hydrophobic balance of the structural components and their mutual physicochemical cross-linking.

[0019] <Third aspect> The application of the conductive hydrogel adhesive described above in fixing the epidermal electrode.

[0020] The application involves coating a molten adhesive onto the interface between the electrode and the skin, which then cools and solidifies to form a conductive adhesive layer. It is suitable for metal electrodes, carbon electrodes, and gel electrodes.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) By adding specific structural components with reversible phase change properties (such as gelatin, collagen, agar, chitosan, sodium alginate, gellan gum, methylcellulose, xanthan gum, etc.) to the adhesive formulation, and further optimizing the content range of each component, a phase change gel with a melting point of 50-80 degrees Celsius and a solidification point of 30-50 degrees Celsius is prepared. The adhesive is immersed in the skin folds in a liquid state, and forms an adhesive effect after cooling and solidification. In this way, commonly available electrodes (including metal electrodes, molded gel electrodes, carbon electrodes, etc.) can be adhered to the skin surface, and solidification and adhesion can be achieved in about 5-15 seconds. The temperature during use is maintained within a range that is tolerable and comfortable for the human body.

[0022] (2) By adding specific conductive components and water-retaining agents to the adhesive formulation and providing preferred combinations between them, such as the combination of betaine and sodium chloride to improve the fluidity of free ions, the combination of sodium citrate and potassium nitrate to improve the concentration of free ions, and the combination of betaine and silver nanoparticles to construct a connected three-dimensional conductive network and form a synergistic conductive pathway, the above combinations can improve the conductivity of the adhesive and reduce the tightness during gel use.

[0023] (3) By combining structural components (such as gelatin and agar; collagen and xanthan gum; gelatin and sodium alginate), the microstructure of the structural components, including the hydrophilic-hydrophobic balance and mutual physicochemical cross-linking, is adjusted. This results in adhesives with stronger adhesion and mechanical strength. The gel prepared by this method can be completely peeled off from the skin and the surface of commercial electrodes after use, without sticking to hair or leaving any residue. Attached Figure Description

[0024] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 These are photographs of the adhesive in Example 1 exhibiting solid and liquid states at different temperatures; Figure 2 Examples of the use of the adhesive in commercial electromyography (EMG) electrodes in Example 1, wherein (a) is a test of a commercial electrode without adhesive assistance; and (b) is a test with adhesive assistance prepared in Example 1. Figure 3 This is a comparison of the adhesive in Example 1 with commercially available adhesives in transcranial stimulation applications; wherein, (a) is the commercially available 3M conductive paste; and (b) is the adhesive prepared according to Example 1. Figure 4 This is a comparison of the adhesive in Example 1 with commercially available adhesives after use in transcranial stimulation applications; where (a) is 3M conductive paste, a commercially available conductive paste; and (b) is the adhesive prepared according to Example 1. Detailed Implementation

[0025] The present invention will be described in detail below with reference to embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several adjustments and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0026] Example 1 A conductive gel adhesive comprises the following components in parts by weight: 10 parts gelatin, 5 parts agar, 23 parts betaine, 60 parts water, and 2 parts sodium chloride.

[0027] The method for preparing the conductive gel adhesive includes the following steps: (1) Add betaine and sodium chloride to water and stir for 30 minutes until completely dissolved; (2) Add gelatin and agar to the solution obtained in step 1 and stir for 5 minutes until homogeneous; (3) The mixture obtained in step 2 is heated to 90 degrees Celsius, and a completely dissolved solution is obtained after one hour; (4) The solution obtained in step 3 is cooled to room temperature to obtain a gel.

[0028] Figure 1 These are photographs showing the adhesive of this embodiment in solid and liquid states at different temperatures; it is solid at 25°C and liquid at 50°C.

[0029] Figure 2This is an example of the use of the adhesive in commercial electromyography (EMG) electrodes in Example 1. (a) shows the test of the commercial electrode without adhesive assistance; (b) shows the test with the adhesive prepared in Example 1. Results show that the signal obtained with the adhesive from Example 1 has better signal intensity and a higher signal-to-noise ratio than the signal obtained directly from the commercial electrode. The commercial electrode is a commercially available Ag / AgCl surface electrode, a circular disc with a diameter of 2 mm and a thickness of 1 mm. During the test, the back of the arm and hand were first wiped clean with an alcohol wipe. Then, the ground electrode was attached to the back of the hand, and the reference electrode and working electrode were attached to the flexor digitorum superficialis (FDS) muscles of the arm. Signal acquisition was performed using a commercial EMG signal acquisition device (model: HKJ-15C, Hefei Huake Electronic Technology Research Institute; acquisition range: 0.5-400Hz; acquisition frequency: 2000Hz). Ten separate samples were collected, and the data were averaged. The signal-to-noise ratio (SNR) was calculated as: SNR (dB) = 201g (AgCl). signal / A noise ), where A signal and A noise These represent the amplitudes of the signal and the background, respectively. A signal and A noise The value can be evaluated using root mean square (RMS) analysis, indicating the fluctuation of the signal over time.

[0030] Figure 3 This paper compares the adhesion of the adhesive used in Example 1 to that of the commercially available 3M conductive paste in transcranial stimulation applications. (a) shows the commercially available 3M conductive paste; (b) shows the adhesive prepared in Example 1. In the transcranial electrical stimulation test, the commercial electrode was a matching Ag / AgCl surface ring electrode, a ring with a diameter of 2 mm and a thickness of 1 mm. During the test, the side of the head was first cleaned, and then the ring electrode was attached to the corresponding acupoint on the head for electrical stimulation. Electrical stimulation was then performed using a commercial electromyography (EMG) signal acquisition device (device model: Starstim 32, Winfu Instruments). The commercially available 3M conductive paste could not successfully fix the electrode and required an electrode cap, while the adhesive provided in Example 1 of this invention could directly fix the commercially available transcranial stimulation electrode.

[0031] Figure 4This is a comparison between the adhesive used in Example 1 and the commercially available 3M conductive paste in transcranial stimulation. (a) shows the commercially available 3M conductive paste; (b) shows the adhesive prepared in Example 1. The specific testing procedure was as follows: First, the test area (F3 / F4 brain region) was cleaned with scalp cleansing, including cleaning with absorbent cotton and alcohol. The commercially available 3M conductive paste and the adhesive prepared in this invention were then bonded to the test area, and dynamic monitoring was conducted continuously for five hours under conditions of 25±2℃ and 50±5% humidity. During this process, simulated head movements (nodding and shaking frequency 1 time / second, 5-minute intervals for 2 minutes, continuous for 30 minutes) and electromagnetic interference control measures (such as Faraday cage shielding) were implemented. Failure was defined as electrode displacement >2mm. Residual amount was tested using the residual area method, and the percentage of residual area was analyzed using ImageJ software after image acquisition. The commercially available 3M™ conductive paste left significant residue after use, while the adhesive provided by this invention could be directly removed without residue.

[0032] Example 2 A conductive gel adhesive comprises the following components in parts by weight: 8 parts gelatin, 2 parts gellan gum, 15 parts sodium citrate, 70 parts water, and 5 parts potassium nitrate.

[0033] The method for preparing the conductive gel adhesive includes the following steps: (1) Add sodium citrate and potassium nitrate to water and stir for 1 hour until completely dissolved; (2) Add gelatin and gellan gum to the solution obtained in step 1, and stir for 20 minutes until homogeneous; (3) The mixture obtained in step 2 is heated to 80 degrees Celsius, and a completely dissolved solution is obtained after one hour; (4) The solution obtained in step 3 is cooled to room temperature to obtain a gel.

[0034] Example 3 A conductive gel adhesive comprises the following components in parts by weight: 15 parts collagen, 5 parts xanthan gum, 10 parts glycerin, 65 parts water, and 5 parts silver nanoparticles.

[0035] A method for preparing a conductive gel fixative includes the following steps: (1) Add glycerin and silver nanoparticles to water and stir for 1 hour until completely dissolved; (2) Add collagen and xanthan gum to the solution obtained in step 1 and stir for 10 minutes until homogeneous; (3) The mixture obtained in step 2 is heated to 90 degrees Celsius, and a completely dissolved solution is obtained after one hour; (4) The solution obtained in step 3 is cooled to room temperature to obtain a gel.

[0036] Comparative Example 1 The difference between this comparative example and Example 1 is that agar is omitted and the amount of gelatin is adjusted to 15 parts.

[0037] Results: When gelatin is used alone as a gelling agent, omitting agar makes its network structure prone to breakage, and the mechanical and adhesive properties of the hydrogel adhesive decrease significantly.

[0038] Comparative Example 2 The difference between this comparative example and Example 1 is that the ratio of gelatin to agar is changed from 10 parts and 5 parts to 2 parts and 2 parts, respectively.

[0039] Result: Insufficient viscosity prevented effective spreading at the interface, resulting in a significant decrease in the mechanical and adhesive properties of the hydrogel adhesive.

[0040] Comparative Example 3 The difference between this comparative example and Example 1 is that betaine was replaced with a water-absorbing resin (Sumitomo SA60N). Because this water-retaining agent competes for moisture with the structural components and cannot bind to them microscopically, the water retention of the hydrogel adhesive is significantly reduced.

[0041] Comparative Example 4 The difference between this comparative example and Example 2 is that potassium nitrate is replaced with calcium nitrate. Because the interaction between calcium ions and structural components is stronger and their ionic ionization decreases, the conductivity of the hydrogel adhesive decreases.

[0042] Comparative Example 5 The difference between this comparative example and Example 3 is that the silver nanoparticles were replaced with graphene. Due to insufficient compatibility between graphene and the structural components, poor microdispersion resulted in decreased conductivity of the hydrogel adhesive.

[0043] Application performance testing: Performance tests were conducted on the hydrogels prepared in each embodiment and comparative example.

[0044] Test method: (1) Tensile test: Uniaxial tensile test was performed on the hydrogel adhesive sample using a universal testing machine (KJ-1065A, Guangdong Kejian). Before the test, the hydrogel sample was cut into dumbbell shape (4×50mm) using a cutter. The test temperature was room temperature, and the tensile rate was 100mm / min. The tensile strength, i.e. the stress at the fracture point, was obtained through the tensile stress-strain curve.

[0045] (2) Adhesion Test: Adhesion was tested using the standard 90-degree peel method. The adhesion of the hydrogel adhesive was tested. Before the test, the adhesive was applied to the skin, and a cloth was used as a backing to fix the adhesive. The adhesion area was a rectangle of 2cm*10cm. The adhesive was stretched to perform a tensile test at a stretching rate of 50mm / min. The adhesive force was calculated by measuring the force required to break the adhesion. The formula is: Adhesive force σ=2F / W, where σ is the adhesive toughness, F is the force required to break the adhesion, and W is the adhesive width (2cm, i.e., the dimension perpendicular to the peel direction).

[0046] (3) Water retention test: The hydrogel sample was treated in a forced-air drying oven for 30 days until constant weight. The sample mass before and after the test was measured and the water content was calculated. Water content (%) = (original sample mass - treated sample mass) / original sample mass × 100.

[0047] (4) Conductivity test: The standard conductivity test method was used. Before the test, the hydrogel adhesive was cut into circular pieces with a diameter of 1 cm and a thickness of 2 mm, and the impedance was tested using an electrochemical workstation (CHI600E). The conductivity was obtained by impedance calculation, and the calculation formula was P=R*S / L, where P is the conductivity, R is the impedance, S is the area of ​​the circular piece, and L is the thickness of the circular piece.

[0048] Table 1

[0049] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A conductive hydrogel adhesive with temperature phase change properties for fixing epidermal electrodes, characterized in that, The components include the following parts by weight: Structural components, 5-20 parts; selected from at least one of gelatin, collagen, agar, chitosan, sodium alginate, gellan gum, methylcellulose, and xanthan gum; 1-5 parts of conductive material; 5-10 parts of water-retaining component; 50-70 parts water.

2. The conductive hydrogel adhesive according to claim 1, characterized in that, The water-retaining component is selected from at least one of betaine, sodium citrate, glycerin, ethylene glycol, propylene glycol, sodium tripolyphosphate, ectoine, sodium pyrrolidone carboxylate, trehalose, and nicotinamide.

3. The conductive hydrogel adhesive according to claim 1, characterized in that, The conductive material is selected from at least one of sodium chloride, lithium chloride, potassium chloride, potassium nitrate, silver nanoparticles, and carbon nanotubes.

4. The conductive hydrogel adhesive according to claim 1, characterized in that, The conductive material and the water-retaining component satisfy one of the following combinations: (A) A combination of betaine and sodium chloride; (B) Combination of sodium citrate and potassium nitrate; (C) Combination of betaine and silver nanoparticles.

5. The conductive hydrogel adhesive according to claim 1, characterized in that, The structural components are one of the following combinations: (a) Gelatin and agar, in a weight ratio of 1-5:1; (b) Gelatin and gelatin, compounded in a weight ratio of 2-8:1; (c) Collagen and xanthan gum, compounded in a weight ratio of 2-4:1; (d) Gelatin and sodium alginate, compounded in a weight ratio of 1-3:

1.

6. A method for preparing a conductive hydrogel adhesive according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Add the water-retaining component and the conductive substance to water and stir until completely dissolved to obtain a premixed solution; (2) Add the structural component to the premixed solution and stir to form a uniform dispersion; (3) Heat the dispersion to a certain temperature and stir at a constant temperature; (4) Cool to room temperature to form a gel.

7. The method for preparing the conductive hydrogel adhesive according to claim 6, characterized in that, In step (3), the heating temperature is 50-90℃ and the stirring time is 30-60 minutes.

8. The use of the conductive hydrogel adhesive as described in any one of claims 1-5 in fixing the epidermal electrode.

9. The application according to claim 8, characterized in that, A molten conductive hydrogel adhesive is applied to the interface between the electrode and the skin, and after cooling and solidification, a conductive adhesive layer is formed.

Citation Information

Patent Citations

  • Hydrogel adhesive and preparation method thereof, negative electrode and battery

    CN119242253A

  • Preparation method of 3D printing thermal reversible hydrogel

    CN112979996A

  • Neural electrode assembly and preparation method thereof, implantation system and storage medium

    CN116250840A

  • Biogel electrode, preparation method and application thereof

    CN118005951A

  • Hydrogel preparation method with adjustable phase change temperature and hydrogel

    CN120059231A

Cited By

  • Preparation method and application of catechol-modified polymer conductive adhesive hydrogel

    CN122541750A